Atomic structural catalogue of defects and vertical stacking in 2H/3R mixed polytype multilayer WS2 pyramids. Issue 22 (28th May 2019) - Ryu, Gyeong Hee; Chen, Jun; Wen, Yi; Zhou, Si; Chang, Ren-Jie; Warner, Jamie H.
Abstract : We examine the atomic structure of chemical vapour deposition grown multilayer WS2 pyramids using aberration corrected annular dark field scanning transmission electron microscopy coupled with an in situ heating holder. Abstract : We examine the atomic structure of chemical vapour deposition grown multilayer WS2 pyramids using aberration corrected annular dark field scanning transmission electron microscopy coupled with an in situ heating holder. The stacking orders and specific types of defects after partial degradation by S and W atomic loss at high temperature are resolved layer-by-layer. Our study of an individual WS2 pyramid with at least six layers, reveals a mixed 2H and 3R polytype stacking. Etching occurred both top and bottom of the WS2 pyramid, which aids in determining the exact vertical layer stacking configurations in the thicker regions. We provide an extensive catalogue of the contrast profiles associated with defects in WS2 as a function of layer number and stacking type, as imaged using ADF-STEM. These results provide extensive details about the identification of a wide range of defects in S2 layers, and the unique ADF-STEM contrast patterns that arise from complex multilayer stacking.